Estrutura e comportamento em solução de copolímeros anfifílicos do tipo poliéter glicol - Marques, Yuri Alencar (2013)
The solution behavior and self-assembly structural phenomena of two industrial amphiphilic polyether glycol block copolymers with different chemical structures and similar cloud points were studied. The raw industrial diol copolymer was subjected to fractionation by preparative liquid chromatography with a size exclusion column (prep-LC-SEC). Prep-LC-SEC did not achieve a molecular mass separation; nonetheless it generated a separation of fractions by means of polarity. Significant heterogeneity of chain polarity of the fractions was demonstrated by CO2 supercritical fluid chromatography (SFC). The temperature and concentration effects of the polymers in polar 2-(2-butoxyethoxy)ethanol and water (25DB) solution were investigated by means of a combination of ATR-FTIR and SAXS techniques. In ATRFTIR analysis, a hypsochromic shift was shown for the O-H absorption peak with an increase in copolymer concentration in solution. This shift was consistently observed in high as well as in low temperatures. Narrowing of the C-O peak width with increasing concentration was demonstrated. A slight bathochromic shift of the C-H peaks was observed as a result of increasing polymer concentration. SAXS evaluation of the copolymers was carried out in concentrated systems. Despite the distinct chemical structures, the scattering curves indicate that the micellar aggregation processes and structural forms of both polyether glycols in solution are significantly similar. SAXS profiles in temperatures above and close to the cloud point revealed the absence of a macromolecular organized structure of the copolymer polyethers in 25DB solution. An investigative fit of the SAXS curves with a hard sphere model (HSM K-T) support the similar solution behavior of the two block copolymers evaluated in this study. The similarities of the aggregation and structural assembly of the two industrial triblock polyether glycols in polar solutions were evidenced. The correlations of the intermolecular interactions and the self-assembly morphology of the copolymer polyethers with the microphase separation temperature, i.e. the cloud point, were demonstrated.